High Assurance Policy-Based Key Management at Low Cost - Acar, Tolga; Nguyen, Lan (Microsoft Research Technical Report, 2014)
Past decade has witnessed the availability of Trusted Platform Modules (TPM) on commodity computers. While the most common use of TPM appears to be BitLocker on Windows OS, server class motherboards have not yet enjoyed a similar TPM deployment base. Recent research and products show that the TPM can provide a level of trust on locally executing software. Nonetheless, TPMs haven’t been utilized in data center cryptographic key management for higher levels of security assurance than software-only techniques. Hardware-based key management has so far been constrained to higher cost add-on hardware. We present a large scale policy-driven cryptographic key manager built with TPM security assurances. We describe our design principles and axioms, architecture and abstractions, security policy, and implementation. We create a role-based security model and express the model with SecPal security policy assertions. We describe our implementation of three roles, actions, resources, SecPal policies and tokens that com- bine them. Finally, we present our implementation results with SecPal proof graphs.